The Implementation Of Modest And Simple Principle To Mahr As A Contribution To The Indonesian Marriage Law - Kasim, Nur Mohamad (Jurnal Hukum & Pembangunan, 2023)
Mahr was one of the groom's provisions to the bride and regulated by the Islamic sharia. Mahr was one of the series in a marriage procession. Islam regarded mahr as the bride's private rights, so it should not be transferred to her guardian or family. Islam defined mahr as the groom's duty, and it should not be violated. The bride would fully authorize mahr. QS. An-Nisa (4) recited, “And give the women (upon marriage) their (bridal) gifts graciously.” The gift was mahr, whose amount was determined on behalf of two parties' agreement, as it should have been voluntarily given. Nevertheless, mahr could be arranged by a modest and simple principle not to burden the groom. During this time, mahr had been arranged by prestige, status, and economic principles. It might restrict the groom's goodwill to marry the bride because the best mahr was the easiest mahr. Although it was actually not one of the compulsories in an Islamic marriage, it was an obligation for the groom. Mahr given to the bride should meet the following requirements: valuable wealth, a sacred object that gave advantages, a non-ghasab object, a non-abstract object/real object.